Análisis del tipo de cambio bilateral y el crecimiento económico de estados unidos sobre las exportaciones no tradicionales de Perú periodo 1980 – 2021 - Masias Rugel, Xiomara de los Milagros (2024)
The present investigation analyzes the bilateral exchange rate and the economic growth of the United States on non-traditional exports from Peru, through macroeconomic variables using an ordinary least squares analysis with annual data during the period 1980 to 2021. The variables that determine More precisely, these exports are: the real bilateral exchange rate, economic growth in the United States. The study concluded that the economic growth of the United States is directly related and presents a positive marginal effect on non-traditional exports of 24.92932. However, the real bilateral exchange rate of the United States presents an inverse relationship in the long term with a marginal effect of 1.837357.